2018
DOI: 10.1039/c8mh00386f
|View full text |Cite
|
Sign up to set email alerts
|

A general salt-resistant hydrophilic/hydrophobic nanoporous double layer design for efficient and stable solar water evaporation distillation

Abstract: A unique hydrophilic/hydrophobic nanoporous double layer structure was designed for efficient and stable solar water evaporation distillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(127 citation statements)
references
References 50 publications
3
121
0
Order By: Relevance
“…In 2018, for the first time, a Janus structure evaporator was proposed for solar steam generation consisting of two functional layers: upper hydrophobic CB-coated polymethylmethacrylate (PMMA) layer as the solar absorber to harness solar as well as robust protector to resist salts accumulation, and bottom hydrophilic PAN layer as water storage to offer enough water supplies to the evaporation (Figure 8a). [140] The results demonstrated that the evaporation rate of the HHNDL structure tends to be stable over 15 day continuous desalination without decay, and there is no salts accumulation observed onto the surface because of the salt blocking of hydrophobic CTSe layer. In spite of the success of above Janus evaporator, most solar absorbers are usually hydrophilic and thus hydrophobic modification approaches are required to be implanted.…”
Section: Strategies For Enhancing Water Evaporation Efficiencymentioning
confidence: 82%
See 2 more Smart Citations
“…In 2018, for the first time, a Janus structure evaporator was proposed for solar steam generation consisting of two functional layers: upper hydrophobic CB-coated polymethylmethacrylate (PMMA) layer as the solar absorber to harness solar as well as robust protector to resist salts accumulation, and bottom hydrophilic PAN layer as water storage to offer enough water supplies to the evaporation (Figure 8a). [140] The results demonstrated that the evaporation rate of the HHNDL structure tends to be stable over 15 day continuous desalination without decay, and there is no salts accumulation observed onto the surface because of the salt blocking of hydrophobic CTSe layer. In spite of the success of above Janus evaporator, most solar absorbers are usually hydrophilic and thus hydrophobic modification approaches are required to be implanted.…”
Section: Strategies For Enhancing Water Evaporation Efficiencymentioning
confidence: 82%
“…Compared with conventional desalination technologies, its greatest advantage is to use sustainable and pollution-free energy source for realizing low-energy desalination. [79] Recently, some reports have showed that the rejection of salt ions was up to 99.5% even under high original salt concentration (100 mg mL −1 ), [62,140] which was even higher than that of various conventional desalination technologies. For instance, the concentrations of four primary ions of Na + , Mg 2+ , K + , and Ca 2+ in the seawater were significantly reduced by orders to 1.41, 0.05, 0.76, and 0.91 mg L −1 in the ascollected distillate (Figure 9a), respectively, which was far below drinking water salinity levels defined by World Health Organization (WHO) and US Environmental Protection Agency (EPA) Standard.…”
Section: Applications Associated With Water Evaporationmentioning
confidence: 98%
See 1 more Smart Citation
“…[10,15] The technology can achieve a solar conversion efficiency over 15%, which is highly competitive, let alone the benefits of program controllability, sustainable productivity, and system upgradability with cheaper and more efficient photovoltaic cells. [23][24][25][26][27][28] Rationally, capitalizing the full potential of solar energy, beyond the limitation of UV light excitation, that are not absorbed by photo catalyst or photovoltaic cells for water splitting will undoubtedly augment the efficiency to further accelerate technological deployment. [17][18][19][20][21][22] Despite immense efforts in designing various composition and structure to optimize the intrinsic activity of catalysts, the progress remains insufficient.…”
mentioning
confidence: 99%
“…[23][24][25][26][27][28] Rationally, capitalizing the full potential of solar energy, beyond the limitation of UV light excitation, that are not absorbed by photo catalyst or photovoltaic cells for water splitting will undoubtedly augment the efficiency to further accelerate technological deployment. [23][24][25][26][27][28] Rationally, capitalizing the full potential of solar energy, beyond the limitation of UV light excitation, that are not absorbed by photo catalyst or photovoltaic cells for water splitting will undoubtedly augment the efficiency to further accelerate technological deployment.…”
mentioning
confidence: 99%